Law Enforcement Strategies of the Sragen Police in Combating Cybercrime Against Children - Prasetyo, Viki Andi; Putri , Hanuring Ayu Ardhani; Zaelani, Muhammad Aziz (Jurnal Ilmu Hukum Kyadiren, 2026)
The rapid development of digital technology has fundamentally transformed patterns of crime against children, thereby necessitating more effective and adaptive prevention strategies by law enforcement agencies. This study is motivated by the increasing vulnerability of children to cyberspace-related crimes and the growing urgency for police institutions to utilize digital platforms as preventive instruments. The objective of this research is to empirically examine the implementation of child crime prevention through digital platforms by the Sragen Police Resort and to analyze the legal, institutional, social, and technological challenges encountered in its execution. This study employs an empirical legal research design with a sociological legal approach, utilizing interviews, observations, and document analysis as primary data collection techniques. The findings indicate that the Sragen Police Resort has implemented preventive measures through social media engagement, cyber patrols, and digitally based public outreach. However, the effectiveness of these initiatives remains constrained by limited digital forensic capacity, inadequate cross-sectoral coordination, and a high incidence of underreporting. This study concludes that strengthening regulatory frameworks, institutional capacity, and inter-agency synergy is a critical prerequisite for enhancing the effectiveness of child crime prevention.